Education on John Dewey’s Pragmatism (Critical Analysis Study of John Dewey's View on Education) - Alif Cahya Setiyadi; Fuad L Anshori; ⁠Moh. Ilham Fahreza (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the concept of John Dewey's Pragmatism Education. As far as the author reads, John Dewey's Education is oriented towards Pragmatism by carrying out the concepts of